Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2022)
Systemic lupus erythematosus (SLE) is a life-threatening autoimmune disease characterized by adaptive immune system activation, formation of double-stranded DNA autoantibodies and organ inflammation. Five patients with SLE (four women and one man) with a median (range) age of 22 (6) years, median (range) disease duration of 4 (8) years and active disease (median (range) SLE disease activity index Systemic Lupus Erythematosus Disease Activity Index: 16 (8)) refractory to several immunosuppressive drug treatments were enrolled in a compassionate-use chimeric antigen receptor (CAR) T cell program. Autologous T cells from patients with SLE were transduced with a lentiviral anti-CD19 CAR vector, expanded and reinfused at a dose of 1 × 106 CAR T cells per kg body weight into the patients after lymphodepletion with fludarabine and cyclophosphamide. CAR T cells expanded in vivo, led to deep depletion of B cells, improvement of clinical symptoms and normalization of laboratory parameters including seroconversion of anti-double-stranded DNA antibodies. Remission of SLE according to DORIS criteria was achieved in all five patients after 3 months and the median (range) Systemic Lupus Erythematosus Disease Activity Index score after 3 months was 0 (2). Drug-free remission was maintained during longer follow-up (median (range) of 8 (12) months after CAR T cell administration) and even after the reappearance of B cells, which was observed after a mean (±s.d.) of 110 ± 32 d after CAR T cell treatment. Reappearing B cells were naïve and showed non-class-switched B cell receptors. CAR T cell treatment was well tolerated with only mild cytokine-release syndrome. These data suggest that CD19 CAR T cell transfer is feasible, tolerable and highly effective in SLE.
CRIS-Team Scopus Importer:2022-09-30

A pair of non‐competing neutralizing human monoclonal antibodies protecting from disease in a SARS‐CoV‐2 infection model - Peter, Antonia Sophia; Roth, Edith; Schulz, Sebastian; Fraedrich, Kirsten; Steinmetz, Tobit; Damm, Dominik; Hauke, Manuela; Richel, Elie; Müller-Schmucker, Sandra; Habenicht, Katharina Marie; Eberlein, Valentina; Issmail, Leila; et al. (European Journal of Immunology, 2021)
TRIANNI mice carry an entire set of human immunoglobulin V region gene segments and are a powerful tool to rapidly isolate human monoclonal antibodies. After immunizing these mice with DNA encoding the spike protein of SARS-CoV-2 and boosting with spike protein, we identified 29 hybridoma antibodies that reacted with the SARS-CoV-2 spike protein. Nine antibodies neutralize SARS-CoV-2 infection at IC50 values in the subnanomolar range. ELISA-binding studies and DNA sequence analyses revealed one cluster of three clonally related neutralizing antibodies that target the receptor-binding domain and compete with the cellular receptor hACE2. A second cluster of six clonally related neutralizing antibodies bind to the N-terminal domain of the spike protein without competing with the binding of hACE2 or cluster 1 antibodies. SARS-CoV-2 mutants selected for resistance to an antibody from one cluster are still neutralized by an antibody from the other cluster. Antibodies from both clusters markedly reduced viral spread in mice transgenic for human ACE2 and protected the animals from SARS-CoV-2-induced weight loss. The two clusters of potent non-competing SARS-CoV-2 neutralizing antibodies provide potential candidates for therapy and prophylaxis of COVID-19. The study further supports transgenic animals with a human immunoglobulin gene repertoire as a powerful platform in pandemic preparedness initiatives.

Author Correction: Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus. - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2023)
EVALuna2:512812

CD19-Targeted CAR-T Cells in Refractory Systemic Lupus Erythematosus: Safety, Efficacy, and Mechanistic Insights from the First Five Patients - Müller, Fabian; Völkl, Simon; Mougiakakos, Dimitrios; Böltz, Sebastian; Aigner, Michael; Gary, Regina; Kretschmann, Sascha; Kharboutli, Soraya; Kleyer, Arnd; Simon, David; Rösler, Wolf; Habenicht, Katharina Marie; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Class switch towards non-inflammatory, spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination - Irrgang, Pascal; Gerling, Juliane; Kocher, Katharina; Lapuente, Dennis; Steininger, Philipp; Habenicht, Katharina Marie; Wytopil, Monika; Beileke, Stephanie; Schäfer, Simon; Zhong, Jahn; Ssebyatika, George; Krey, Thomas; et al. (Science immunology, 2022)
RNA vaccines are efficient preventive measures to combat the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. High levels of neutralizing SARS-CoV-2 antibodies are an important component of vaccine-induced immunity. Shortly after the initial two mRNA vaccine doses, the immunoglobulin G (IgG) response mainly consists of the proinflammatory subclasses IgG1 and IgG3. Here, we report that several months after the second vaccination, SARS-CoV-2–specific antibodies were increasingly composed of noninflammatory IgG4, which were further boosted by a third mRNA vaccination and/or SARS-CoV-2 variant breakthrough infections. IgG4 antibodies among all spike-specific IgG antibodies rose, on average, from 0.04% shortly after the second vaccination to 19.27% late after the third vaccination. This induction of IgG4 antibodies was not observed after homologous or heterologous SARS-CoV-2 vaccination with adenoviral vectors. Single-cell sequencing and flow cytometry revealed substantial frequencies of IgG4-switched B cells within the spike-binding memory B cell population [median of 14.4%; interquartile range (IQR) of 6.7 to 18.1%] compared with the overall memory B cell repertoire (median of 1.3%; IQR of 0.9 to 2.2%) after three immunizations. This class switch was associated with a reduced capacity of the spike-specific antibodies to mediate antibody-dependent cellular phagocytosis and complement deposition. Because Fc-mediated effector functions are critical for antiviral immunity, these findings may have consequences for the choice and timing of vaccination regimens using mRNA vaccines, including future booster immunizations against SARS-CoV-2.<br

Dysregulation of the B lymphocyte compartment in patients with chronic graft-versus-host disease - Habenicht, Katharina Marie; Bootz, Anna; Schneider, Alexandra; Schäfer, Simon; Hoffmann, P.; Winkler, Julia; Wolff, D.; Winkler, Thomas (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Expansion of Plasmablasts at Day 90 after Allogeneic Stem Cell Transplantation Predict Chronic Gvhd - Habenicht, Katharina Marie; Bootz, Anna; Schäfer, Simon; Vasova, Ingrid; Fante, Matthias; Schneider, Andrea; Rehli, Michael; Hoffmann, Petra; Rösler, Wolf; Edinger, Matthias; Herr, Wolfgang; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

SARS-CoV-2 in severe COVID-19 induces a TGF-β-dominated chronic immune response that does not target itself - Ferreira-Gomes, Marta; Kruglov, Andrey; Durek, Pawel; Heinrich, Frederik; Tizian, Caroline; Heinz, Gitta Anne; Pascual-Reguant, Anna; Du, Weijie; Mothes, Ronja; Fan, Chaofan; Frischbutter, Stefan; Habenicht, Katharina Marie; et al. (Nature Communications, 2021)
The pathogenesis of severe COVID-19 reflects an inefficient immune reaction to SARS-CoV-2. Here we analyze, at the single cell level, plasmablasts egressed into the blood to study the dynamics of adaptive immune response in COVID-19 patients requiring intensive care. Before seroconversion in response to SARS-CoV-2 spike protein, peripheral plasmablasts display a type 1 interferon-induced gene expression signature; however, following seroconversion, plasmablasts lose this signature, express instead gene signatures induced by IL-21 and TGF-β, and produce mostly IgG1 and IgA1. In the sustained immune reaction from COVID-19 patients, plasmablasts shift to the expression of IgA2, thereby reflecting an instruction by TGF-β. Despite their continued presence in the blood, plasmablasts are not found in the lungs of deceased COVID-19 patients, nor does patient IgA2 binds to the dominant antigens of SARS-CoV-2. Our results thus suggest that, in severe COVID-19, SARS-CoV-2 triggers a chronic immune reaction that is instructed by TGF-β, and is distracted from itself.
CRIS-Team Scopus Importer:2021-04-09